SYMPOMS OF EPIDIDYMITIS, TREATMENT AND EPIDIMIOLOGY (International journal of artificial intelligence, 2024)
Epididymitis is a medical condition characterized by inflammation of the epididymis, a curved structure at the back of the testicle.[1] Onset of pain is typically over a day or two.[1] The pain may improve with raising the testicle.[1] Other symptoms may include swelling of the testicle, burning with urination, or frequent urination.[1] Inflammation of the testicle is commonly also present.